2019
DOI: 10.1007/978-3-030-24254-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Synergies and Trade-Offs of National Conservation Policy and Agro-Forestry Management Over Forest Loss in Argentina During the Last Decade

Abstract: One reason for the decline of natural forest is that many ecosystem services (ESs) are usually not priced and values were only considered provisioning services. Argentina enacted the National Law 26,331/07, which regulates protection, enrichment, restoration and management of native forests and its environmental services. The objective is to determine the ecological and sociopolitical factors that influence the dynamics of forest cover loss before and after the law implementation and discuss the effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
0
16
0
3
Order By: Relevance
“…Finally, it is important to highlight that the HFI is highly compatible with other land-use management decision making tools that actually were implemented in Patagonia Argentina, e.g. ordination processes for the sustainable management and conservation of the native forests (see Martínez Pastur et al, 2020). This simple methodology can be useful for those responsible of planning that are land use planners looking for a complement to existing tools rather than requiring a radical rethink of how conservation planning or management is approached.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is important to highlight that the HFI is highly compatible with other land-use management decision making tools that actually were implemented in Patagonia Argentina, e.g. ordination processes for the sustainable management and conservation of the native forests (see Martínez Pastur et al, 2020). This simple methodology can be useful for those responsible of planning that are land use planners looking for a complement to existing tools rather than requiring a radical rethink of how conservation planning or management is approached.…”
Section: Discussionmentioning
confidence: 99%
“…Si bien los bosques nativos no son necesariamente los ecosistemas más diversos ni los que brindan mayores servicios ecosistémicos, han recibido mayor atención de la sociedad para mejorar su protección e implementar prácticas de uso sostenible (e.g., . En la actualidad, la valoración de los bosques maduros es mayor debido a los impactos del manejo forestal intensivo y a los cambios o transformaciones en el uso del suelo (e.g., conversión de bosques en actividades agroganaderas) (Martínez Pastur et al 2020). Estas actividades cambiaron la cobertura de las especies forestales nativas, impactaron sobre la biodiversidad y simplificaron el paisaje, con la consiguiente pérdida de provisión de algunos servicios ecosistémicos (Messier et al 2015).…”
Section: R������unclassified
“…those values without market value) and biodiversity conservation in the managed forests (e.g. Native Forest Law 26,331 of Argentina) (Martínez Pastur et al 2020b). In this framework, variable retention harvesting offers an alternative that combines timber and in-situ conservation (Martínez Pastur et al 2009 reported that legacies maintained in managed stands varied according to the different forest management plans, from small patches (e.g., aggregates of 3,000 m² to a couple of hectares) to isolated trees (e.g., dispersed retention) with desirable characteristics for conservation (e.g.…”
Section: Silvicultural Experiencesmentioning
confidence: 99%